Epilepsy in a population of 6000 re-examined: secular trends in first attendance rates, prevalence, and prognosis. Issue 5 (May 1995) - Cockerell, O C; Eckle, I; Goodridge, D M; Sander, J W; Shorvon, S D
Abstract : It is important to document changes in the vital statistics of epilepsy in the general population so that the success or failure of prevention and treatment can be assessed and health provisions planned. A population of 6000 persons was studied 10 years apart to determine secular trends in the prevalence and prognosis of epilepsy. The lifetime prevalence of all patients with one or more afebrile seizures was 20.3/1000 (95% CI 16.9-24.3) in 1983 and 21.0/1000 (95% CI 17.6-25.1) in 1993. The prevalence of active epilepsy was 5.3/1000 (95% CI 3.6-7.5) in 1983 and 4.3 (95% CI 2.8-6.3) in 1993. To assess trends in incidence rates the annual first attendance rates were measured from 1964 to 1993. Annual first attendance rates in children (age < 20 years) have declined from 152.4/100, 000 (90% CI 106.0-212.9) in the years 1974-83, to 60.9/100, 000 (90% CI 33.0-103.3) in the years from 1984-93, suggesting that the incidence of epilepsy in children is falling. Also noteworthy was the first attendance rates for epilepsy in elderly people (61-80 years) in the years 1984-93, of 82.0 (90% CI 38.5-154.0), higher than in any other age group. This increase in the number of elderly patients with epilepsy is important, and has health planning implications, especially with the overall increase in the total elderly population. There was, however, no evidence that prognosis has significantly altered in the past 40 years.